Sonographic Assessment of Isthmocele and Its Obstetric Complications in Subsequent Pregnancies: A Pictorial Review - Agarwal, Prateek; Agarwal, Rajesh Kumar; Purohit, Arushi (Indian Journal of Radiology and Imaging, 2024)
Cesarean scar defect represents a significant pathology attributed to the rising prevalence of cesarean deliveries. While not commonplace, these lesions can give rise to severe obstetric consequences during subsequent pregnancies. Given the potential complications, it is advisable to screen for uterine niches using transvaginal ultrasound (TVUS) or contrast-enhanced TVUS for individuals planning to conceive. Surgical repair and correction of these lesions can be crucial in averting obstetric and perinatal complications in future pregnancies. Furthermore, timely sonographic evaluation and reporting of isthmocele-related obstetric complications can help avoid serious issues.
Keywords: cesarean section; isthmocele; placenta accreta spectrum; cesarean scar pregnancy; retained products of conception; sonography